2010
DOI: 10.5575/geosoc.116.321
|View full text |Cite
|
Sign up to set email alerts
|

美濃帯西部,舟伏山地域の上部三畳系珪質ミクライト

Abstract: Siliceous micrite crops out in close association with bedded chert and nodular chert in the Middle Jurassic melange of the Mino terrane in the Mt. Funabuseyama area, central Japan. The siliceous micrite and chert form a characteristic lithologic association of a siliceous micrite-chert facies ca. m thick in a bedded chert succession. The siliceous micrite is light gray and occurs as thin, lenticular beds in thin-bedded chert and as irregular-shaped blocks in thick-bedded to massive chert. The siliceous micrite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The depositional age of micritic limestone remains unconstrained due to the replacement of radiolarians with recrystallized calcite. However, the mineral assemblage and texture of the micritic limestone resemble Upper Triassic siliceous micrites in Middle Jurassic to Early Cretaceous accretionary complexes of Southwest and Central Japan, which represent an appearance of calcareous nannoplankton in the pelagic region of Panthalassa Ocean during the Late Triassic (Onoue & Yoshida, 2010; H. Sano et al., 2010, 2017; Yoshida & Onoue, 2008). Because terrigenous materials are absent, the BLM may originate from the mixing of micritic limestone and basalt in a submarine landslide on the lower slope of a seamount above the CCD (Figure 12a) (e.g., Matsuda & Ogawa, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The depositional age of micritic limestone remains unconstrained due to the replacement of radiolarians with recrystallized calcite. However, the mineral assemblage and texture of the micritic limestone resemble Upper Triassic siliceous micrites in Middle Jurassic to Early Cretaceous accretionary complexes of Southwest and Central Japan, which represent an appearance of calcareous nannoplankton in the pelagic region of Panthalassa Ocean during the Late Triassic (Onoue & Yoshida, 2010; H. Sano et al., 2010, 2017; Yoshida & Onoue, 2008). Because terrigenous materials are absent, the BLM may originate from the mixing of micritic limestone and basalt in a submarine landslide on the lower slope of a seamount above the CCD (Figure 12a) (e.g., Matsuda & Ogawa, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Funabuseyama. The former three localities are where Sano et al (2010) reported Upper Triassic siliceous micrite. Wakita, 1988;Yamagata, 1989Yamagata, 1989 .…”
mentioning
confidence: 99%
“…primitius E. quadrata . Numbered sections are as follows: 1, siliceous micrite of the Kugo Limestone of this study; 2, siliceous micrite-chert facies of the Mino Belt, tentatively named Shiraiwadani Limestone in this paper (after Sano et al, 2010); 3, siliceous micritechert facies of the Tamba Belt, tentatively named Ashimidani Limestone in this paper (after Kosaka and Ishiga, 1996); and 4, radiolarian bedded chert facies of the middle part of the Lower Triassic to Upper Jurassic ocean plate stratigraphy of the Mino and Tamba belts (after Wakita, 2012). Table 3 3 , , 1979; , 1984 Table 3 2010 2010 Jones et al, 1993et al, Ichiyama et al, 2008et al, , 1983, 19832 Ozawa and Nishiwaki, 1992, 2000 Igo, 1989Igo, 2000Igo, , 1989Igo, 2010 Fig.…”
mentioning
confidence: 99%